Assessment of Perceived Stress, Social Inhibition, And Negative Affectivity in Elderly Patients with Peripheral Vertigo: A Case-Control Study (Journal of Pharmaceutical Negative Results, 2022)
Background: Vertigo is a common problem in the elderly age group. One biggest issues with vertigo are that it is difficult to diagnose and identify.Objective: The present study was aimed to assess the perceived stress, social inhibition, and negative affectivity in elderly patients with peripheral vertigo.Materials and methods: A total of 30 elderly participants with peripheral vertigo were part of the study after obtaining written informed consent. 30 age and gender-matching controls were also recruited. Both male and female participants were recruited in the study. Assessment of perceived stress was done using a standard questionnaire. DS14 questionnaire was used to assess the negative affectivity and social inhibition scores in the participants.Results: There were significantly higher perceived stress scores in the cases when compared with the controls. There were significantly higher scores of social inhibition in the cases when compared with the controls. There were significantly higher scores of negative affectivity in the cases when compared with the controls.Conclusion: The study results support that there are significantly higher scores of stress, negative affectivity, and social inhibition in the patients with peripheral vertigo when compared with the controls. Further, detailed studies are recommended in this area.